2021
DOI: 10.1016/j.plas.2021.100018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 on field and office workforce in construction industry

Abstract: The COVID-19 outbreak is the greatest global health crisis in many years. It has had a dramatic effect on workforces and workplaces all around the world, as it has spawned a massive change in the working atmosphere and raised the level of employees’ concerns about their mental health and physical wellbeing. The construction industry has been significantly affected by the COVID-19 pandemic and has been challenged to improve the safety and wellbeing of its workforce. The objectives of this study are to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(103 citation statements)
references
References 43 publications
7
93
2
1
Order By: Relevance
“…Our results about telework and entrapment are in accordance with the literature, but there are also other situations involving on-site workers, unemployed persons and layoff workers that might lead to entrapment [ 65 , 66 ]. It is important to note that unemployment and layoff workers were analyzed together due to the reduced number of unemployed participants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results about telework and entrapment are in accordance with the literature, but there are also other situations involving on-site workers, unemployed persons and layoff workers that might lead to entrapment [ 65 , 66 ]. It is important to note that unemployment and layoff workers were analyzed together due to the reduced number of unemployed participants.…”
Section: Discussionsupporting
confidence: 91%
“…According to the literature, people that needed to work on-site during the COVID-19 pandemic feared a possible exposure to the virus at work [ 65 ] and felt anxious about being infected by the virus [ 67 ]. Our findings suggest that this type of worker has high levels of imagined surveillance, and that this negatively impacts anxiety and stress, but that it is not directly correlated to mobile expectations.…”
Section: Discussionmentioning
confidence: 99%
“…NT employment rates went from 129,900 in May 2020 to 131,300 in May 2021, which reflects an increase of 1.07% increase in the overall employment across various sectors of the state [60]. However, the employment to population ratio dipped by 0.1%, and the participation rate dipped by 2.3%.…”
Section: Unemployment Rates In States and Territoriesmentioning
confidence: 97%
“…The modes of transmission for the SARS-CoV-2 (COVID-19 causing) virus are similar to those of the flu, SARS-CoV-1, MERS, and influenza viruses, which include contact, droplet, airborne, fomite, fecal-oral, blood borne, mother-to-child, and animal-to-human transmission [6]. Pamidimukkala et al [7] concluded that the virus can be transmitted from person-to-person and causes symptoms that include fever, dry cough, fatigue, and shortness of breath. Due to its strong infectious nature, extended incubation period, difficulty in detection, and vagueness in transmission modes, COVID-19 is becoming a very difficult disease to control [8].…”
Section: Introductionmentioning
confidence: 98%